Combining ability for resistance to rice yellow mottle virus disease in interspecific and intraspecific rice Genotypes - Munganyinka, Esperance; Edema, Richard; Lamo, Jimmy; Gibson, Paul; Rukundo, Placide (African Journal of Crop Science, 2015)
Estimates of combining ability for resistance to rice yellow mottle virus disease (RYMV) were obtained in the green house of National Crops Resources Research Institute, Uganda. The study involved forty-one F2’s diallel crosses and their five intraspecific and four interspecific parental lines. Effects of both general combining ability (GCA) and specific combining ability (SCA) for RYMV reactions were significant, with a preponderance of GCA effects. Of parental lines used in this study, Naric 1, Nerica 6 and WAC 116 were good combiners for transferring resistance genes to their progenies. In this study, most genotypes with good resistance were good general combiners expect Gigante, that despite its good mean performance, combined badly for resistance to RYMV. The crosses with the best resistance were Naric 1x Gigante, Naric 1x Nerica 6, Nerica 6 x Nerica 4 and Nerica 1 x Nerica 6. From this study, we suggest that selection of parents as donors for resistance should consider both GCA and parental performance. On the basis of predominant additive genetic effects observed in the present study, we believe that combinations of interspecific parents may be used to produce rice varieties resistant to RYMV, and that selection in early selfing generations should be effective.
Keywords: Rice; Resistance; Yellow mottle virus; Combining ability; GCA; SCA